Implementación de las normas internacionales de información financiera (NIIF) para la Cooperativa de Ahorro y Crédito Futuro Salcedense de la provincia de Cotopaxi, cantón Salcedo en el periodo 2014 - Guevara Vimos, Sandra Elizabeth (2015)
International Financial Reporting Standards are a set of technical rules that establish accounting criteria for registration and preparation of financial statements, therefore this work is focused on the application of International Financial Reporting Standards at Cooperative of Saving and credit Salcedense Future, it will allow the institution to present a clear and accurate information about its business in a given period, at the first part of the work the theoretical foundations were supported by development of research, as well as detailed methods and techniques for analysis and data collection in which the surveys and interviews for staff working were applied in the institution which helped to publicize the shortcomings that cooperative has at the end of the research it was determined that the application of International Financial Reporting Standards it is viable and the cooperative may submit Financial Economically value information and it will enable at making decision, thus financial information is standardized nationally and internationally.